The Effect of Export, Islamic Mutual Fund, and Labor Force on Economic Growth in Indonesia - Ranti Silviani; Imsar Imsar; Khairina Tambunan; Muhammad Ikhsan Harahap (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2022)
This study aims to determinethe effect of exports, islamic mutual funds, and the labor force on economic growth. This is quantitative research with associative approach. The data used were secondary data which was obtained through the official website of the Central Statistics Agency (CSA) and the Financial Services Authority (FSA). The study used multiple linear regression analysis with the Ordinary Least Square (OLS) method by the E-Views version 10 program. From the results obtained, it can be explained that exports had a significant positive effect on Indonesian's economic growth.Islamic mutual funds had a negative significant effect while the labor force had a positive significant effect the labor force on Indonesia's economic growth. In the F (simultaneous) test there was a simultaneous significant effect among exports, islamic mutual funds, and the labor force on Indonesia's economic growth. Adjusted R-squared = 0.863602. This showed that the independent variables are able to provide an explanation about 86.3% of the dependent variable. Meanwhile, 13.7% more wasexplained by other variables outside the model.